The simultaneous analysis of eight essential trace elements in human milk by ICP-MS - Mohd Taufek, Nor Hidayah; Cartwright, David William; Davies, Mark W.; Hewavitharana, Amitha K; Koorts, Pieter J.; Shaw, Paul Nicholas; Sumner, Ronald; Lee, Eugene; Whitfield, Karen M. (Springer New York, 2016)
Trace elements are commonly present as components of metabolic enzymes, hormones and antioxidants in human milk. Previous studies have reported single or few elements in relatively large volumes of human milk using complex, time-consuming and expensive methods involving microwave-assisted acid digestion and extraction using tetramethylammonium hydroxide at various temperatures. We report here a validated alkaline dissolution method using ethylenediaminetetraacetic acid, ammonia solution, isopropanol and Triton X-100 to simultaneously determine trace elements in 0.2 mL samples of human milk by inductively coupled plasma mass spectrometry (ICP-MS). The trace elements zinc (Zn), copper (Cu), selenium (Se), manganese (Mn), iodine (I), iron (Fe), molybdenum (Mo), bromine (Br), chromium (Cr), cobalt (Co), lead (Pb), nickel (Ni), silver (Ag), cadmium (Cd), arsenic (As), bismuth (Bi), aluminium (Al),antimony (Sb), vanadium (V), thallium (Tl) and uranium (U)were detected, and the method was applied quantitatively to 12 samples of human milk. The results for method validation showed good sensitivity, accuracy and repeatability for Zn, Cu, Se, Mn, I, Fe, Mo and Br. The mean±SD of these elements in the above human milk samples (μg/L) were 1390.6 ± 211.5, 220.8 ± 32.9, 14.3 ± 5.8, 1.37 ± 0.14, 113.5 ± 17.1, 47.3± 99.9, 0.37± 0.12 and 812.6 ± 127.7, respectively. This method is precise, reliable, straightforward and cost effective in the determination of trace elements simultaneously in small sample volumes of human milk. Method application permits routine monitoring of several elements and the ongoing assessment of trace element nutrition in breast milk. It is the first method to highlight the relatively high Br levels present in human milk